Best Answer

Related Post

Spread the word

Digg this post

Bookmark to delicious

Stumble the post

Add to your technorati favourite

Subscribes to this post

2 Comments Already

mygif
tootoot Said,
February 5th, 2011 @11:28 pm  

5x^2+5x=3
5x^2 + 5x – 3 = 0
using the quadratic formula, we let a=5, b=5, c=-3

then x = { -5 +- [5^2 - 4 * 5 * (-3)]^(1/2) } / (2 *5)
= { -5 +- [25 + 60]^(1/2) } / 10
= { -5 +- [85]^(1/2) } / 10

the answer is a

mygif
numbr1TXfan Said,
February 5th, 2011 @11:44 pm  

first set it equal to 0
5x^2+5x-3
x= -5 +/- square root of 5^2-4(5)(-3)/ 2(5)
x= -5 +/- suare root of 25+60/ 10
” ” 85/10
looks like A!

Leave Your Comments Below

Please Note: All comments will be hand modified by our authors so any unsuitable comments will be removed and you comments will be appreared after approved